2021
DOI: 10.47419/bjbabs.v2i01.35
|View full text |Cite
|
Sign up to set email alerts
|

Serum and urinary soluble α-Klotho levels in patients with chronic kidney disease

Abstract: Background: Chronic kidney disease is an epidemic global health problem that leads to death. To prevent any disease progression and treatment, the diagnosis must be made in the early stage by studying renal damage. Klotho is a protein found in many organs of the human body, but it is mainly abundant in the kidney. This study aimed to evaluate klotho's clinical significance as an additional biomarker for diagnosing chronic kidney disease in its early stages.   Methods: One hundred subjects were included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Immunization is one of the programs being used as an indicator of minimum service standards in the health sector. The implementation of immunization is regulated by the Regulation of the Minister of Health Number 12 of 2017 and Number 4 of 2019, under which immunization services must be carried out completely and precisely according to the standards [8][9][10][11][12][13][14][15][16]. Indonesian policy requires every baby (aged 0 -11 months) to receive complete basic immunization (CBI) consisting of 1 dose of Hepatitis B, one dose of BCG, three doses of DPT-HB-HiB, four doses of polio drop, and one dose of measles/MR.…”
Section: Introductionmentioning
confidence: 99%
“…Immunization is one of the programs being used as an indicator of minimum service standards in the health sector. The implementation of immunization is regulated by the Regulation of the Minister of Health Number 12 of 2017 and Number 4 of 2019, under which immunization services must be carried out completely and precisely according to the standards [8][9][10][11][12][13][14][15][16]. Indonesian policy requires every baby (aged 0 -11 months) to receive complete basic immunization (CBI) consisting of 1 dose of Hepatitis B, one dose of BCG, three doses of DPT-HB-HiB, four doses of polio drop, and one dose of measles/MR.…”
Section: Introductionmentioning
confidence: 99%
“…Since its appearance in Wuhan, China, in December 2019, the corona-19 virus (Covid- 19) has rapidly spread globally [1][2][3]. There have not been adequate studies on the immunological response to COVID-19 infection, and it is unclear if people who have recovered from the virus will become infected again.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the risk factors for chronic kidney disease were age, race, obesity, diabetes, low birth weight, high blood pressure, and family history [ 14 ]. The risk of CKD morbidity and mortality remains considerably high, with CKD patients usually receiving renal replacement therapy, such as dialysis and kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%